Methodology for the Evaluation of Career Decision Making Skills in Rural Schools. Final Report - Malheur Intermediate Education District, Vale, OR.; Malheur Intermediate Education District, Vale, OR. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1977)
As part of a larger program of a consortium of six rural Oregon counties (SIXCO), a study was conducted to select instruments which provided a measure of career decision-making skills and to utilize these instruments on populations of students who received varying types of guidance processes in their school programs. Of the twenty-nine instruments recommended by the reviewing panels, two were selected: the Career Development Inventory (CDI) for grade 9 and the Career Maturity Inventory (CMI) for grades 10-12. During the fall and spring terms of 1976-77, selected students were tested with these instruments. The types of schools selected for the project included those with the guidance cadre for purposes of developing career decision making, a guidance processes program with all teachers being involved, and a program with no formal guidance. Both the CMI and CDI fall term test scores served as the base for assessing the effects of guidance processes for the various grade levels during the school year. With the exception of the results for CDI Scale B (resources for exploration), no statistically significant differences were found to exist across the treatment groups. These results were considered to have established the product worth of the assessment instruments for evaluation of career decision-making skills in rural schools. (BM)
Sponsoring Agency: Bureau of Occupational and Adult Education (DHEW/OE), Washington, DC.
Sponsoring Agency: Oregon State Dept. of Education, Salem.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Achievement Tests; Career Awareness; Career Counseling; Career Development; Career Education; Consortia; Decision Making Skills; Evaluation; Evaluation Methods; Grade 12.; Guidance Programs; Measurement Instruments; Rural Schools; Secondary Education; Test Validity; Vocational Maturity; Career Development Inventory -- Career Maturity Inventory; Oregon; Reports, Research